Development of a Diagnostic Assessment Instrument to Measure the Mathematical Reasoning Ability of Junior High School Students - Siti Nurul Sajdah; Kana Hidayati (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aimed to produce a diagnostic assessment instrument for mathematical reasoning ability of junior high school students, describe the quality of diagnostic assessment instruments, and describe the profile of mathematical reasoning ability of junior high school students in Barru Regency based on the diagnostic assessment developed. This study used a development research approach referencing instrument development procedure from Edi Istiyono. Test and measurement subjects included 534 grade VIII students in Barru Regency. Data analysis included content validity through expert judgement analyzed using Aiken's V coefficient; construct validity through Confirmatory Factor Analysis (CFA); reliability estimation using Cronbach's Alpha coefficient; and item analysis based on item response theory with GPCM model. Results showed: (1) Construction of diagnostic assessment instruments for mathematical reasoning ability developed based on five aspects: compiling conjectures, providing reasons or evidence, drawing conclusions, examining validity of arguments, and finding patterns and making generalizations; (2) Instrument quality reviewed from content validity with V Aiken declared valid; construct validity tested through CFA, resulting in 19 items indicating loading factor > 0.35; instrument reliability using Cronbach Alpha in high category; (3) Mathematical reasoning ability results were categorized as very high (18%), high (21%), low (41%), and very low (20%).